Working Toward a Socially Just Future in the ELA Methods Class. (June 2019) - Fowler-Amato, Michelle; LeeKeenan, Kira; Warrington, Amber; Nash, Brady Lee; Brady, Randi Beth
This review of literature highlights the efforts teacher educators and researchers have made over the past 18 years to work toward social justice in secondary English language arts (ELA) preservice teacher (PT) education. Drawing on Dantley and Green's framework for social justice leadership, we highlight the work that teacher educators have engaged in to support secondary ELA PTs in developing (a) indignation/anger for justice through exploring beliefs about students and themselves, (b) a prophetic and historical imagination through broadening understandings about teaching and learning, and (c) accountability to students and communities through university-to-classroom transitions. We close this article by drawing on this framework to honor what we, as a field, have accomplished while acknowledging the efforts that still need to be made in working toward justice in secondary ELA PT education and, ultimately, in the schools and communities in which our PTs teach.